2004
DOI: 10.1002/jnr.20048
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor, brain‐derived neurotrophic factor, and neurotrophin‐3 are sorted to dense‐core vesicles and released via the regulated pathway in primary rat cortical neurons

Abstract: Neurotrophins (NTs) play an important role in the modulation of synaptic transmission and in morphological changes in synaptic structures. Although there is agreement that brain-derived neurotrophic factor (BDNF) is sorted to large dense-core vesicles (LDCVs) and released via the regulated secretory pathway, there has been some dispute regarding the mode of secretion of nerve growth factor (NGF) and neurotrophin-3 (NT-3), two structurally related members of the NT family. In this study, we examined the subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 40 publications
1
37
1
Order By: Relevance
“…The intracellular fate and the sites of secretion of the other NTs, however, remained a highly controversial issue. Data from two laboratories suggested a similar intracellular targeting and release of all NTs (Heymach et al, 1996;Griesbeck et al, 1999;Wu et al, 2004). In contrast, NT-3, NT-4, and NGF were described by others to be released predominantly via the constitutive pathway (Mowla et al, 1999;Farhadi et al, 2000, Hibbert et al, 2003.…”
Section: Intracellular Localization Of Neurotrophinsmentioning
confidence: 84%
See 2 more Smart Citations
“…The intracellular fate and the sites of secretion of the other NTs, however, remained a highly controversial issue. Data from two laboratories suggested a similar intracellular targeting and release of all NTs (Heymach et al, 1996;Griesbeck et al, 1999;Wu et al, 2004). In contrast, NT-3, NT-4, and NGF were described by others to be released predominantly via the constitutive pathway (Mowla et al, 1999;Farhadi et al, 2000, Hibbert et al, 2003.…”
Section: Intracellular Localization Of Neurotrophinsmentioning
confidence: 84%
“…However, because of the low expression levels of endogenous BDNF, many details concerning BDNF localization were derived from BDNF-or BDNF-GFP-overexpressing CNS neurons. These studies indicated that BDNF is targeted to secretory granules in dendrites and axons of CNS neurons (Haubensak et al, 1998;Wu et al, 2004). Furthermore, BDNF vesicle clusters are found in the vicinity of active synapses and are released in response to synaptic stimulation Kohara et al, 2001;Kojima et al, 2001).…”
Section: Intracellular Localization Of Neurotrophinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical neurons were isolated from embryonic day-16 embryos of Sprague-Dawley rats according to the protocol of Wu et al (27). Briefly, cerebral cortices were dissected, dissociated with 0.25% trypsin (Invitrogen), triturated, and passed through 70-m-pore-size meshes.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA for the myc-tagged BDNF was subcloned into pAdTrackCMV for the generation of recombinant adenovirus (pAdEasy system) (He et al, 1998;Wu et al, 2004). myc-BDNF was subcloned with SalI and XbaI, and large-scale virus preparations were performed in human embryonic kidney HEK293 cells using the cesium chloride banding method.…”
Section: Methodsmentioning
confidence: 99%